2018
DOI: 10.1097/j.pain.0000000000001298
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical and vasomotor evidence for interdependency of TRPA1 and TRPV1-evoked nociceptive responses in human skin: an experimental study

Abstract: The TRPA1 and TRPV1 receptors are important pharmaceutical targets for antipruritic and analgesic therapy. Obtaining further knowledge on their roles and interrelationship in humans is therefore crucial. Preclinical results are contradictory concerning coexpression and functional interdependency of TRPV1 and TRPA1, but no human evidence exists. This human experimental study investigated whether functional responses from the subpopulation of TRPA1 nociceptors could be evoked after defunctionalization of TRPV1 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 88 publications
(126 reference statements)
1
11
0
Order By: Relevance
“…54,55 In the present study, the provided heat stimuli (48°C in experiment 2) were deliberately kept so brief that no sensory sensitization was present in the secondary area. 56 In line with the present findings, Ward et al 57 delivered 48°C heat counterstimuli immediately adjacent to the itch provocation site and observed inhibitory results approximately in between the present effects of homotopic and heterotopic intrasegmental counterstimulation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…54,55 In the present study, the provided heat stimuli (48°C in experiment 2) were deliberately kept so brief that no sensory sensitization was present in the secondary area. 56 In line with the present findings, Ward et al 57 delivered 48°C heat counterstimuli immediately adjacent to the itch provocation site and observed inhibitory results approximately in between the present effects of homotopic and heterotopic intrasegmental counterstimulation.…”
Section: Discussionsupporting
confidence: 90%
“…Skin, wherein secondary hyperalgesia is present, is known to be resistant to experimentally evoked itch (both histaminergic and nonhistaminergic) . In the present study, the provided heat stimuli (48 °C in experiment 2) were deliberately kept so brief that no sensory sensitization was present in the secondary area . In line with the present findings, Ward et al .…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, by direct recordings of spikes from dural nerves, we found that the firing was preferentially mediated by activation of TRPV1 receptors (Koroleva et al, 2017 ). Notably, TRPV1 and TRPA1, two members of the TRP receptors family are often co-localized (Nielsen et al, 2018 ). Moreover, there are data that these channels can be heteromerized (Fischer et al, 2014 ; Weng et al, 2015 ) suggesting that H 2 S might act in employing these channels complex.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent work suggests that TRPA1 nociceptive responses in human skin strongly depend on intact capsaicin-sensitive, TRPV1 + fibers [21]. In their work, Nielsen and colleagues investigated whether functional responses from the subpopulation of TRPA1 + nociceptors could be evoked after defunctionalization of TRPV1 + nociceptors by cutaneous application of high-concentration capsaicin.…”
Section: Some Of the Most Recent Findings Regarding The Role Of Trmentioning
confidence: 99%
“…In their work, Nielsen and colleagues investigated whether functional responses from the subpopulation of TRPA1 + nociceptors could be evoked after defunctionalization of TRPV1 + nociceptors by cutaneous application of high-concentration capsaicin. It has been found that ablation of cutaneous capsaicin-sensitive afferents caused consistent and equal inhibition of both TRPV1- and TRPA1-provoked responses assessed psychophysically and by imaging of vasomotor responses [21].…”
Section: Some Of the Most Recent Findings Regarding The Role Of Trmentioning
confidence: 99%